2007
DOI: 10.1111/j.1532-5415.2007.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Endothelial Function in Alzheimer's Disease: Is Alzheimer's Disease a Vascular Disease?

Abstract: Endothelial function is impaired in patients with AD. Endothelial function was worse in patients with severe AD. These findings provide evidence that vascular factors have a role in the pathogenesis of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 28 publications
2
106
0
Order By: Relevance
“…Therefore, the only independent factor that causes damage in endothelial function was advanced age. It has been proved that endothelial dysfunction occurs in many diseases including chronic renal failure, heart failure, hypertension, diabetes mellitus, hypercholesterolemia, rheumatic diseases, and Alzheimer disease [8][9][10][11][12][13][14][15] . Therefore, patients with these diseases were excluded in order to examine the independent effect of age on endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the only independent factor that causes damage in endothelial function was advanced age. It has been proved that endothelial dysfunction occurs in many diseases including chronic renal failure, heart failure, hypertension, diabetes mellitus, hypercholesterolemia, rheumatic diseases, and Alzheimer disease [8][9][10][11][12][13][14][15] . Therefore, patients with these diseases were excluded in order to examine the independent effect of age on endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many commentators have noted that a number of vascular risk factors are likewise risk factors for Alzheimers, and that many measures which boost endothelial nitric oxide function are linked to decreased risk for this disorder. [25][26][27][28][29][30][31][32][33][34][35] Recent research has established that hypoxia boosts neuronal expression of BACE1 (a.k.a. beta-secretase), a protease whose activity can be rate-limiting for the production of the amyloid-beta peptides thought to drive the inflammatory process in Alzheimers.…”
mentioning
confidence: 99%
“…In addition, recent data have shown that endothelial function is impaired in AD patients, suggesting that such dysfunction might represent a link between vascular and beta-amyloid hypothesis of Alzheimer's disease [52][53][54]. The endothelium is a monolayer of endothelial cells lining the lumen of the vascular beds and is mechanically and metabolically located, separating the vascular wall from the circulation and the blood components [55].…”
Section: Discussionmentioning
confidence: 99%